2005
DOI: 10.3758/bf03192694
|View full text |Cite
|
Sign up to set email alerts
|

A Web-based study of cerebral asymmetry for perception of emotion

Abstract: Many studies have examined cerebral asymmetry via lateralized presentation of stimuli using specialized software. Because these studies typically require extensive control over variables such as stimulus exposure duration, size, location, and so forth, they are not easily transferred to the World Wide Web. The present study replicated a free-vision, chimeric faces task via the Internet, using HTML and JavaScript. Previous results had shown that right-handed participants tend to perceive a chimeric face with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Presumably, however, most mothers in the present study chose holding side according to their handedness, otherwise there would probably have been more lefthanded mothers holding on the left arm just like the right-handed mothers. This is because even left-handed individuals are mostly lateralised to the right for face perception*albeit to a lesser extent*(e.g., Levy et al, 1983;Rueckert, 2005), and accordingly tend to cradle infants on the left too, if there is no concurrent motor task to be done (Salk, 1960).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Presumably, however, most mothers in the present study chose holding side according to their handedness, otherwise there would probably have been more lefthanded mothers holding on the left arm just like the right-handed mothers. This is because even left-handed individuals are mostly lateralised to the right for face perception*albeit to a lesser extent*(e.g., Levy et al, 1983;Rueckert, 2005), and accordingly tend to cradle infants on the left too, if there is no concurrent motor task to be done (Salk, 1960).…”
Section: Discussionmentioning
confidence: 98%
“…Righthanded individuals typically show a left bias. That is, they tend to pick the image with the happy or female face half on the left-hand side (from the observer's point of view) as the one that looks more happy or feminine (e.g., Ashwin, Wheelwright, & Baron-Cohen, 2005;Burt & Perrett, 1997;Drebing, Federman, Edington, & Terzian, 1997;Levy, Heller, Banich, & Burton, 1983;Luh, Rueckert, & Levy, 1991;Mattingley, Bradshaw, Nettleton, & Bradshaw, 1994;Nicholls & Roberts, 2002;Rueckert, 2005). In our study the left-arm-held individuals showed the typically found left bias, whereas the right-arm-held individuals had a significantly reduced left bias, indicating that their right hemisphere was less dominant for face processing.…”
mentioning
confidence: 98%
“…Chiang et al, 2000;Christman & Hackworth, 1993;Coolican et al, 2008;Coronel & Federmeier, 2014;Levy et al, 1983;Rueckert, 2005) though some have investigated all six basic emotions (e.g. Bourne, 2010Bourne, , 2011Workman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Sackheim & Gur, 1978), as 4 well as Levy, Heller, Banich and Burton (1983), who examined asymmetries in emotional facial expression by vertically dividing images of faces and creating mirrored composites from each half of the face, as a task to evaluate hemispheric asymmetries in emotional perception. The task has been used extensively in the years since (Bourne, 2008;2010, 2011Chiang, Ballantyne, & Trauner, 2000;Christman & Hackworth, 1993;Coolican, Eskes, McMullen, & Lecky, 2008;Coronel & Federmeier, 2014;Luh, 1998;Luh, Rueckert, & Levy, 1991;Mattingley, Bradshaw, Nettleton, & Bradshaw, 1994;Rahman & Anchassi, 2012;Rueckert, 2005;Workman, Peters, & Taylor, 2000). In a typical version of the task, neurologically healthy participants are presented with two faces, one placed above the other.…”
Section: Introductionmentioning
confidence: 99%
“…As has been repeatedly demonstrated, most people show a left-bias, that is, a tendency to choose the chimera with the facial expression on the left (e.g. Ashwin, Wheelwright, & Baron-Cohen, 2005;Burt & Perrett, 1997;Levy et al, 1983;Luh, Rueckert, & Levy, 1991;Nicholls & Roberts, 2002;Rueckert, 2005). For the second experiment, the Gender test, the two chimeras in each pair were made by combining a female with a male face half.…”
Section: Introductionmentioning
confidence: 99%